KEMANDIRIAN KEUANGAN DI ERA OTONOMI DAERAH PADAPEMERINTAH KABUPATEN SUBANG - Zaenal Hirawan (Universitas Sultan Ageng Tirtayasa, 2016)
This research aims to find out the level financial autonomy and ability Subangregency government in the period 2010 to 2014. This research uses descriptive method.Based on the analysis and calculation of the ratio of the level of financial independenceSubang regency in the period 2010-2014 is 13.75% with the level of assessment is lessgood. For the fiscal capacity to manage a budget said to be good with a value of101.59%.